Effect of different condition on voltage generation and thermal gradient from road pavement using thermoelectric generator - Muhammad Syadza Sharuddin; Azdiana Md. Yusop; Ahmad Sadhiqin Mohd Isira; Khairun Nisa Khamil (Penerbit Universiti Kebangsaan Malaysia, 2020)
Thermal energy harvesting is an interesting topic to be studied due to its advantage of being easily to be acquired, whether from natural sources or from waste heat. Road pavement is one of the example of waste heat sources which can be easily harvested because asphalt road is paved everywhere to facilitate land transportation. The thermal energy from a road can be collected by using a thermoelectric generator (TEG). TEG operates based on the Seebeck effect; when there are temperature differences between two dissimilar electrical conductors, potential differences will be generated. Harvesting thermal energy from the road using TEG does not only provide a clean, renewable source of energy but also can save cost. The government does not have to build electricity poles along the road to power up road lamps and traffic light, which can cost a fortune, especially in rural areas. This research aims to investigate factors that can affect thermoelectric generator energy harvesting from asphalt road, which includes, TEG configuration, TEG cooling technique, and thermal conductivity. Pavement samples were built with aluminium and copper plates installed to collect thermal energy and were tested with different conditions. The final result shows that thermoelectrics with 4x1 configuration provides the highest voltage output with 142.7 mV. The TEG cooling technique using a water tank generates the highest output voltage with 281 mV. Copper plate, which has higher thermal conductivity than aluminium generates more output voltage with 36.9 mV of voltage differences between them.